Accident-Prone Locations on National Roads in Kupang Regency, East Nusa Tenggara Province - Widjajanti, Endang (Riviera Publishing, 2023)
This study aimed to identify and formulate recommendations for improvements to Accident-Prone Locations (LRK) in Kupang Regency, East Nusa Tenggara Province. The approach methodology used includes collecting secondary data on accidents from the police and primary data through field surveys to analyze and rank the severity of accidents. The ranking is done through the value of the Equivalent Accident Number (EAN) and Upper Limit Control (UCL). The analysis results show that there are 18 points of Accident Prone Locations on the national road in Kupang Regency. These namely locations have an EAN value above the BKA and UCL values. A motorcycle is the dominant type of vehicle involved in an accident, and the dominant cause of accidents is the driving factor. The formulation of recommendations for improvement was carried out for 3 locations with the highest EAN values, namely Jl. Oesapa-Oesao Km 5, Km 1 and Km 4. For these three locations, the necessary treatment recommendations were formulated. This research has implications in helping identify and prioritize the most accident-prone locations. The study can also encourage the development or improvement of roads, sidewalks, street lighting, traffic signs, or other necessary infrastructure elements to enhance traffic safety in LRK.